Evaluation of the Diagnostic Performance of Lung Ultrasound Compared to Chest X-rays for Diagnosis of Pneumonia in Children - Stadler, Jacob A M (Department of Public Health and Family Medicine, 2020)
Pneumonia remains a global health priority in children. It is the leading cause of death in children outside the neonatal period, over 90% of which occur in low-resource settings, and a major cause of morbidity, accounting for over 100 million episodes globally each year. Early, correct diagnosis is a modifiable factor which can potentially improve pneumonia outcomes. Current guidelines recommend the use of clinical signs and symptoms alone to make a diagnosis of pneumonia in low risk, ambulatory cases with clinically mild disease. However, clinical diagnosis lacks specificity and may lead to antibiotic overuse and drive antibiotic resistance. Addition of chest X-ray (CXR) to diagnostic algorithms improves specificity, but CXR use is limited by radiation exposure and relatively high costs, limiting access in low-resource settings. Current guidelines therefore reserve CXR for moderate to severe disease and hospitalised cases, even in well-resourced settings. Lung ultrasound (LUS) is a promising imaging modality which uses no radiation, is less costly than CXR and can improve the time to results when used as a point-of-care tool by clinicians outside the radiology department. These characteristics make LUS, at least theoretically, a potential option either as add-on screening test aimed at decreasing unnecessary antibiotic prescription or as a lower risk, lower cost definitive diagnostic test capable of replacing CXR, or both. The objective of this study was to understand the role of LUS as a diagnostic test for pneumonia in children by performing a structured literature review and metaanalysis summarizing the current evidence comparing diagnostic performance of LUS and CXR, and by reporting previously unpublished data from the Drakenstein Child Health Study comparing diagnostic performance of LUS and CXR for pneumonia in children in a resource-constrained, African setting.